(untitled) (Fiep Bulletin - online, 2011)
> This study aimed to profile the employees of the University Veiga de Almeida in Cabo Frio-RJ, aiming to deploy the project Quali-UVA, a project of this type of gymnastics or compensatory pause aimed at improving the health and quality of life These officials. A questionnaire was developed with closed questions about what they feel physically and psychologically during and after the workday. It was found that 75% had an emotional stress and 60% of physical stress, 76% reported discomfort in the spine, 17.5% in upper limbs and 29% in the lower limbs, 82% had a good sleep quality and 68% work more seats, 16% standing and 12% in both positions. Through this profile has been deployed to gymnastics, with excellent acceptance and attendance of officials, so after three months of this practice will be a re-evaluation and through these results will be a review, and for this analysis may occur adjustments or innovations in design Quali-rays, whose purpose is to improve health and quality of life of these workers. . KEYWORDS: Physical fitness, health and quality of life